(untitled) (International Journal of Engineering and Computer Science, 2014)
The main concept of this project is to reduce the weight of automotive drive shaft which is done through the fabrication of Al-Si matrix reinforced with SiC-Cenosphere composite material by stir casting with varying percentage of Cenosphere. Aluminium metal matrix composite have been used in many automotive components because of their properties such as low weight, corrosion free, high specific stiffness, ability to produce complex shapes and high specific strength etc. The effect of weight % of Cenosphere is studied and is used for Automotive drive shaft application. In automobiles the drive shaft is mainly used for the transmission of motion from the engine to the differential. The modeling of the drive shaft assembly was created using CATIA software. In present work an attempt has been to estimate deflection, stresses under subjected boundary conditions, analysis are carried out by Abaqus.